Baromembrane methods for separation of disillery stillage - Zmievskiy, Yuriy; Dzyazko, Yulia; Kornienko, Ludmila; Zakharov, Volodymyr; Ustinov, Olexandr; Mironchuk, Valeriy (My University, 2017)
The paper considers the processing of grain distillery stillage by ultrafiltration and reverse osmosis. The results of experimental studies using the membrane UPM-10 and KS-M (RM NanoTech, Russia) at different pressures and temperatures are presented. An hardware-technological scheme for the processing of grain distillery stillage with the successive application of ultrafiltration and reverse osmosis is proposed.У роботі розглянуто питання переробки зернової барди ультрафильтрацією та зворотним осмосом. Наведено результати експериментальних досліджень з використанням мембрани УПМ-10 і КС-М (РМ Нанотех, Росія) при різних тисках і темпетарурах. Запропоновано апаратурно-технологічну схему переробки барди з послідовним застосуванням ультрафільтрації та зворотного осмосу.
Keywords: distillery stillage; membrane; ultrafiltration; reverse osmosis; барда; мембрана; ультрафільтрація; зворотний осмос; кафедра технологічного обладнання та комп’ютерних технологій проектування